2006
DOI: 10.1007/s11249-006-9027-6
|View full text |Cite
|
Sign up to set email alerts
|

A two-phase flow approach to cavitation modelling in journal bearings

Abstract: Cavitation has been extensively treated in numerical models for lubrication using boundary conditions in the pressure equation, and several criteria are available. However, an inappropriate choice can lead to imprecise results, thus having serious implications for performance prediction. This work proposes the numerical solution for lubrication analysing the changes suffered by the lubricant along a journal bearing, considering the release of gas from the liquid and the existence of a two-phase flow. Results o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
21
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(21 citation statements)
references
References 28 publications
0
21
0
Order By: Relevance
“…Kumar and Booker [30] derived a solution for two-phase flow in journal bearings which modifies the Elrod model [14] and is a widely cited cavitation algorithm. Grando et al [31] developed a two-phase model for journal bearings by considering the interaction between liquid and gas properties and phase dissolution. Bayada and Chupin [32], Bruyere et al [33], and van Odyck and Venner [34] have all developed models investigating two-phase flows in lubricated contacts.…”
Section: Introductionmentioning
confidence: 99%
“…Kumar and Booker [30] derived a solution for two-phase flow in journal bearings which modifies the Elrod model [14] and is a widely cited cavitation algorithm. Grando et al [31] developed a two-phase model for journal bearings by considering the interaction between liquid and gas properties and phase dissolution. Bayada and Chupin [32], Bruyere et al [33], and van Odyck and Venner [34] have all developed models investigating two-phase flows in lubricated contacts.…”
Section: Introductionmentioning
confidence: 99%
“…Although the first studies concerning the lubrication of the compressor sliding parts neglected the presence of refrigerant dissolved in the oil Rigola et al, 2003;Cho and Moon, 2005;Couto, 2006), they undoubtedly have set the foundations for the more recent class of lubrication models that considered the effect of a lubricant mixture composed of refrigerant and oil. Among these studies, Grando et al (2006b) proposed simplified lubrication models for journal bearings considering the interaction between the oil and the refrigerant and the existence of a gas/liquid two-phase flow in the lubricant film. Grando et al Their results indicated an increase of friction losses followed by a reduction in load capacity due to the presence of gaseous refrigerant dispersed in the lubricant film.…”
Section: Introductionmentioning
confidence: 99%
“…Some researchers have focused on the lubricating characteristics of the mixture: Jonsson (1999), Chul Na, Chun and Han (1997), Grando, Priest and Prata (2006). Other researchers have studied the transient processes of absorption and separation (outgassing) of refrigerant in oil, which is useful, for example, to estimate the concentration of refrigerant in the oil stored inside the compressor in the start-up condition: Silva (2004) and Fukuta et al (2005).…”
Section: Introductionmentioning
confidence: 99%